Preparation of Activated Carbon from Helhelok Stones by Chemical Activation - Tareq, Alarqam Z.; Hussein, Mohammed S.; Abdujabar, Pyman A. (Science Journal of University of Zakho, 2018)
In his study activated carbon was prepared from Helhelok stones as a raw material by using chemical activation with zinc chloride (ZnCl2) as a chemical agent with the concentration 40% for 25h at (25⁰C±2). The optimum conditions were approved in having carbonization temperature 400ᵒC for 1h to get a maximum percentage of yield 56%. Other properties of the prepared activated carbon were also studied such as pH, ash content, density, moisture content, conductivity, iodine number and methylene blue dye absorbance. Eventually the prepared activated carbon in this work has obtained good characteristics that make it play an essential role in industrial uses and compared it with commercial standard sample from B. D. H Company.
Keywords: Activated Carbon; Helhelok; Chemical activation; Zinc chloride